Achiral aromatic solvent-induced assembly of 3-D homochiral porous 3d–4f heterometallic-organic frameworks based on isonicotinic acid. Issue 40 (3rd October 2017) - Jin, Hong-Guang; Hong, Xu-Jia; Tan, Hao-Chong; Wei, Qin; Lin, Xiao-Ming; Cai, Yue-Peng
Abstract : Via induction of achiral aromatic solvents, two 3-D monochiral 3d–4f MOFs (1 and2 ) from the ligand HIN without any chiral auxiliary are uncommonly constructed. And the results show homochirality of1 and2 are enantiopurity rather than enantiomeric excess. Abstract : Via induction of achiral aromatic solvents, two 3-D monochiral 3d–4f MOFs (1 and2 ) from the ligand HIN without any chiral auxiliary are uncommonly constructed. The results show that the homochiral compounds1 and2 are enantiopure rather than exhibiting enantiomeric excess. Obviously, this work has brought major synthetic advancement in homochiral framework materials of great significance.